Acanthostachys calcicola (Bromeliaceae, Bromelioideae), a new species from a limestone outcrop in Tocantins State, Brazil - Marcusso, Gabriel Mendes [UNESP]; Monro, Alexandre K.; de Melo, Pablo Hendrigo Alves [UNESP]; Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2020)
A new species of bromeliad, Acanthostachys calcicola, a third taxon for the genus, is here described. A. calcicola was discovered during field work in the limestone outcrops of south-eastern Tocantins, central Brazil. It is most similar to A. strobilacea, but differs from it in petal colour and length, and exserted stamens and pistil. A conservation assessment classifies A. calcicola as endangered (EN) with extinction.
Keywords: Bambuí; Bromeliad; Cerrado; Conservation assessment; Karst; Neotropical Region; Northern Brazil; Poales; Saxicolous